Analisis Perbedaan Antara Laba Akuntansi dan Laba Fiskal Terhadap Persistensi Laba, Akrual, dan Aliran Kas pada Perusahaan Perbankan yangTerdaftar di Bursa Efek Jakarta - SUBEKTI DJAMALUDDIN; HANDAYANI TRI WIJAYANTI; RAHMAWATI RAHMAWATI (The Indonesian Journal of Accounting Research, 2013)
The research aims to examine the role of book-tax differences in indicating the persistence of earnings, accruals, and cash flows for one period ahead earnings. This study also examines whether the level of book-tax differences influences investor's assessments of future earnings persistence. The hypothesis in the alternative form are (1) pre-tax earnings persistence for firms with large (positive or negative) book-tax differences is lower than pre-tax earnings persistence for firms with small book-tax differences; (2) The persistence of the accruals component of earnings for future earnings is lower for firms with large (positive or negative) book-tax differences relative to firms with small book-tax differences; (3) The expectation of pre-tax earnings persistence reflected in stock prices for the accrual component of pre-tax earnings is consistent with observed persistence of accruals for firms with relatively large book-tax differences.The sample of this study was banking companies listed in Jakarta Stock Exchange (JSX) within the period of 2000-2005. The data was collected using purposive sampling method. The amount of the sample was 20 banking. The statistic method using  pooled regression.The results of this study showed that firms with large (positive or negative) book-tax differences have earnings and the accruals component of earnings that are less persistent than firms with small book-tax differences; and the stock prices fail fully reflect the information on the accruals component of earnings and cash flows. Investors appear to underestimate the accrual component of earnings and cash flows when firm-years have large book-tax differences.